(untitled) (Quest Journal of Management and Social Sciences, 2020)
Background: As fears of the corona virus pandemic (also known as the COVID-19 Pandemic) continue to spread around the world, Boma’s global network hosted an unprecedented online summit on the 23rd and 24th of March 2020, to discuss the early lessons learnt about this pandemic with regards to education and explore specific plans of action to address it. The summit inspired this study and its major findings show that COVID-19 has necessitated drastic changes in the education system. Objective: To explore new ways in which teachers can continue teaching the children using non-traditional means during the COVID-19 lockdown period and after; to assess the attitude of parents/guardians to the re-opening of schools after COVID-19 in terms of children’s safety; and examine the challenges posed by COVID-19 to children’s education during the lockdown period. Methods: This research is based on an exploratory design given the immediacy, novelty and emergency associated with COVID-19. This study seeks to have a better understanding of the existing problems relating to children in their education during the lock down period. The design utilizes both primary and secondary data collection methods. Results: The data of this study indicate that it is feasible to offer distance education to children in Zimbabwe despite the existence of COVID-19. Thestudy also indicates that changes to the education system are inevitable and the education system will never be the same after COVID-19. Conclusion: The study concludes that COVID-19 has had a telling effect on education in Zimbabwe and the lasting changes will remain with the system even after the lockdown period.